Time's mouth : a novel - Lepucki, Edan (Counterpoint, 2023)
"Ursa possesses a very special gift. She can travel through memory and revisit her past. After she flees her hometown for the counterculture glory of 1950s California, the intoxicating potential of her unique ability eventually draws a group of women into her orbit and into a ramshackle Victorian mansion in the woods outside Santa Cruz. But Ursa's powers come with a cost. Soon this cultish community of sisterhood takes an ominous turn, prompting her son, Ray, and his pregnant lover, Cherry, to flee their home for Los Angeles and reinvent themselves far from Ursa's insidious influence. But escaping their past won't be so easy. A series of mysterious events forces Cherry to abandon their baby, leaving Ray to raise Opal alone. Now a teenager and still heartbroken over the abandonment of the mother she never knew, Opal must journey into her own past to reveal the generations of secrets that gave rise to the shimmering source of her family's painful legacy."--